2007
DOI: 10.1002/marc.200700330
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Poly(methyl methacrylate) Model Compounds at Constant Elevated Temperature Studied via High Resolution Electrospray Ionization Mass Spectrometry (ESI‐MS)

Abstract: The products of the thermal degradation at 95 °C over 10 months of ω‐saturated and non‐saturated poly(methyl methacrylate) (pMMA) model compounds were identified with high accuracy via quadrupole ion trap and quadrupole ion trap‐time of flight (Q‐ToF) mass spectrometry. Analysis of the samples taken via these techniques indicated that degradation of vinyl terminated pMMA proceeds via the incorporation of oxygen via the formation of ethylene oxide type end groups, which subsequently rearrange under the expulsio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 31 publications
5
55
0
1
Order By: Relevance
“…No other products expected from the literature (other than the acid and aldehyde side groups) are present in the thermal or UV degradation of pBA. The non-radical degradation cycle proposed in our previous publications [1,41] is seen to some extent in pBA, the only exception being species F which falls just outside the acceptable error range. In addition pBA demonstrates crosslinking, especially under UV radiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No other products expected from the literature (other than the acid and aldehyde side groups) are present in the thermal or UV degradation of pBA. The non-radical degradation cycle proposed in our previous publications [1,41] is seen to some extent in pBA, the only exception being species F which falls just outside the acceptable error range. In addition pBA demonstrates crosslinking, especially under UV radiation.…”
Section: Resultsmentioning
confidence: 99%
“…[33,34,[38][39][40] Our previous publications clearly demonstrated that degradation mechanisms cannot necessarily be extrapolated from other studies under different conditions. [1,41] The present study follows on from these recent publications, examining the degradation behaviour of pBA and pHEMA under the worst-case conditions likely to be experienced by a surface coating on a roof exposed to the harsh Australian environment. In addition, it is also instructive to compare the degradation of pBA and pHEMA with that of pMMA in order to better understand the structure-performance relationships of the different polymers.…”
Section: Introductionmentioning
confidence: 99%
“…145 It was found that terminal unsaturation is necessary to enable degradation at these comparably low temperatures, in which case a cyclic non-radical mechanism is operative during thermal degradation. These studies therefore complement earlier pyrolysis studies at much increased temperatures.…”
Section: Polymer Degradationmentioning
confidence: 99%
“…Many studies on the degradation of polymers have appeared in the literature. 26,27 However, the utilization of high-resolution instrumentation or extensive MS experiments has not been fully explored. The majority of MS-based polymer investigations have been conducted in the area of free radical polymerization to deepen the knowledge of reaction mechanisms.…”
mentioning
confidence: 99%